Bruce's Big Storm - Higgins, Ryan T. (Los Angeles ; Disney Hyperion, 2019)
Grumpy Bruce the bear does not like neighbors, but is forced to help when a big storm draws them all to his home.
Keywords: Neighbors -- Juvenile fiction; Forest animals -- Juvenile fiction; Bears -- Juvenile fiction; Storms -- Juvenile fiction; Neighbors -- Fiction; Forest animals -- Fiction; Bears -- Fiction; Storms -- Fiction; Humorous Stories